Transition state analysis of Pyranose 2-Oxidase from Peniophora sp. - Ibrahim Ali , Noorbatcha; Ramli, Siti Khairani; Salleh, Hamzah Mohd. (2013)
Significant interest has been aroused for the use of pyranose 2-oxidase (P2Ox) as a catalyst in biotechnological applications particularly in biofuel and food technology. Understanding the transition state of this enzyme offers greater possibility to improve the catalytic activity of this enzyme and thus speeding the industrial processes. The main purpose of this study is to identify and characterize the transition states for the catalytic reaction of P2Ox from white-rot fungus Peniophora sp.. The complete path for the oxidation reaction catalyzed by P2Ox was investigated using the PM7 semi-empirical method with MOZYME function as implemented in the MOPAC 2012 (Molecular Orbital PACkage) program. The results of this study was consistent with the experimental method where appreciable conformational changes can be seen in the loop of residues 454-461 which was anticipated to be functions as a gatekeeper to allow the substrate to pass into the active center.